The Time is Right - an ICT framework for Networked Learning - Morris, Terry (Proceedings of the International Conference on Networked Learning, 2002)
The paper describes the evolution of a networked learning system applicable to teacher professional development and the education of full-time degree students within New Zealand during the years 1993 - 2001